Activity of intestinal carbohydrases responds to multiple dietary signals in nestling House sparrows - Brzek, Pawel (2013)
The ‘adaptive modulation hypothesis’ predicts that activity of digestive enzymes should match the amount of their substrates in diet. Interestingly, many passerine birds do not adjust the activity of intestinal carbohydrases to dietary carbohydrate content. It is difficult to assess the generality of this rule, because in some studies passerines fed on low-carbohydrate and high-lipid diet showed reduced activity of intestinal carbohydrases. However, as carbohydrase activity may be inhibited by high dietary lipid content, it is unclear whether observed effects reflected lack of induction by the low carbohydrate levels or suppression by the high lipid levels. Here, we isolated the specific effects of dietary carbohydrate and lipid on carbohydrases. We hand-fed house sparrow nestlings on diets with 25% starch and 8% lipid (diet HS), no starch and 20% lipid (HL), or 25% starch and 20% lipid (HSL). Our results show that activity of intestinal carbohydrases is simultaneously induced by dietary carbohydrates and decreased by dietary lipid, although the latter effect seems stronger. Activities of maltase and sucrase summed over the total intestine decreased in the order HS>HSL>HL. We observed a complex interaction between diet composition and intestinal position for mass-specific activity of these enzymes, suggesting site-specific responses to changes in digesta composition along the intestines caused by digestion and absorption. We re-interpret results of earlier studies and conclude that there is no unequivocal example of adaptive modulation of intestinal carbohydrases by dietary carbohydrate in adult passerine birds, whereas the present experiment confirms that nestlings of at least some species possess such capacity.